Extraction and Characterization of Cellulose from Arabica Spent Coffee Grounds - Raymond Hamidy; Hans Rachman; Jaclyn Regina Anggara; Joko Sulistyo; Nyoman Puspa Asri (Jurnal IPTEK, 2025)
Global coffee production generates significant amounts of spent coffee grounds (SCG), often discarded, creating environmental challenges. Cellulose, a major component of SCG, can be extracted for industrial applications, such as food packaging and bioplastics. This research aims to determine the optimal cellulose purification time for maximizing purity and characterize the physicochemical properties of the extracted cellulose for food industry use. The study investigates the effect of different purification times on cellulose purity. The highest purity (74.40%) was obtained at 180 minutes, with the extracted cellulose showing high crystallinity and favorable properties, such as low moisture content (3.49%), water absorption capacity (6.17%), and bulk density (0.2871 g/cm³). Characterization using SEM revealed the morphology of cellulose crystals, and analysis (Carr’s index: 15.33%, Hausner ratio: 1.1811) confirmed the material’s suitability for biocomposites in food applications. Color analysis (L*: 76.34, C*: 28.52, h*: 16.46, WI: 62.94) also highlighted the material’s potential for use in food formulations. This research provides valuable data for further applications of cellulose derived from SCG.